Optimal Design of Turnover Mechanism for Beakers Subassembly in Blended Fabric Quantitative Detecting System - Zhou Mingxing; Meng Zhuo; Sun Xudong (Jixie chuandong)
According to the functional requirement of beakers subassembly in blended fabric quantitative detecting system,a planar six-bar mechanism composed by two oscillating guide bar mechanisms is selected for achieving flip function. The angular displacement,angular velocity and angular acceleration of the guide bar are achieved by establishing kinematical equations of the six-bar mechanism. According to the special consideration of vibration performance when turning over beakers subassembly,a constrained optimization model for solving the minimum acceleration fluctuation is built. The constrained optimization problem is solved by complex method in MATLAB,and the results are displayed after optimization. When considering the stability improvement of beakers subassembly turnover movement in blended fabric quantitative analysis system,the research conclusions achieved here have important practical significance.